Edukasi Pemberantasan Sarang Nyamuk (PSN) Sebagai Upaya Pencegahan DBD - Tika Dhefiana; Andi Daramusseng; Hansen (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2023)
Abstract The case of Dengue Fever in East Kalimantan has significantly increased especially in Samarinda for the last two years. Educational programs are essential to create awareness in disease prevention and improvement of community health. The main purpose of this community educational program is to give basic knowledge and understanding for the residents of RT 27 Kelurahan Air Hitam Kecamatan Samarinda Ulu on the preventive measures for Dengue Fever that are simple and effective. Methods used to deliver this program are in the form of presentations, discussions as well as Q&A sessions. Based on the results on using the Wilcoxon Analysis, it showed significant differences in meaningful a score pretest and posttest knowledge of dengue fever (p= 0,01<0,05), and paired t-test shows differences meaningful a score pretest and posttest education PSN (p=0,00<0,05). The expected outcomes of counselling and educational programs is to increase public awareness and understanding of preventative measures of Dengue Fever in their household and community. Keyword :